Therapeutic effects and mechanism of human amnion-derived mesenchymal stem cells on hypercoagulability in a uremic calciphylaxis patient - Anning Bian; Xiaoxue Ye; Jing Wang; Ming Zeng; Jiayin Liu; Kang Liu; Song Ning; Yugui Cui; Shaowen Tang; Xueqiang Xu; Yanggang Yuan; Zhonglan Su; et al. (Renal Failure)
Calciphylaxis is a rare cutaneous vascular disease that manifests with intolerable pains, non-healing skin wounds, histologically characterized by calcification, fibrointimal hyperplasia, and microvessel thrombosis. Currently, there are no standardized guidelines for this disease. Recent studies have recognized a high prevalence of thrombophilias and hypercoagulable conditions in calciphylaxis patients. Here, we report a case of uremic calciphylaxis patient whom was refractory to conventional treatments and then received a salvage strategy with intravenous and local hAMSC application. In order to investigate the therapeutic mechanism of hAMSCs from the novel perspective of hypercoagulability, coagulation-related indicators, wound status, quality of life and skin biopsy were followed up. Polymerase chain reaction (PCR) was performed to determine the distribution of hAMSCs in multiple tissues including lung, kidney and muscle after infusion of hAMSCs for 24 h, 1 week and 1 month in mice aiming to investigate whether hAMSCs retain locally active roles after intravenous administration. Improvement of hypercoagulable condition involving correction of platelet, D-dimer and plasminogen levels, skin regeneration and pain alleviation were revealed after hAMSC administration over one-year period. Skin biopsy pathology suggested regenerative tissues after 1 month hAMSC application and full epidermal regeneration after 20 months hAMSC treatment. PCR analysis indicated that hAMSCs were homing in lung, kidney and muscle tissues of mice even until tail vein injection of hAMSCs for 1 month. We propose that hypercoagulability is a promising therapeutic target of calciphylaxis patients, which can be effectively improved by hAMSC treatment.